THE ROLE OF CHORAL CONDUCTING IN THE DEVELOPMENT OF UNIVERSITY STUDENTS’ MUSICAL AURAL SKILLS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the educational role of choral conducting in developing the musical aural skills of university students. Musical hearing is approached as a complex professional competence rather than merely the ability to distinguish pitches and intervals. It encompasses tonal and harmonic awareness, rhythmic perception, sensitivity to timbre and dynamics, musical memory, inner hearing, and the ability to anticipate, analyse, and evaluate musical sound.The study is based on an integrative theoretical review and comparative examination of international research concerning aural training, choral singing, conducting gestures, vocal–auditory feedback, sight-singing, and technology-supported choral practice. The analysis indicates that choral conducting creates a multidimensional educational environment in which students read and interpret a score, construct an internal representation of the intended sound, communicate musical ideas through gesture, monitor individual vocal parts and the ensemble as a whole, identify performance problems, and make informed corrective decisions.The findings suggest that choral conducting contributes to the integrated development of pitch discrimination, intonation control, polyphonic listening, harmonic awareness, musical memory, audiation, and auditory self-monitoring. The article also proposes a four-stage pedagogical model that includes diagnostic assessment, formation of an internal auditory image, polyphonic listening and correction, and reflective self-evaluation. It is concluded that choral conducting should be taught not only as a system of manual beat patterns but also as an interconnected auditory, analytical, motor, interpretative, and pedagogical discipline.